2021
DOI: 10.1186/s13046-021-02202-3
|View full text |Cite
|
Sign up to set email alerts
|

Loss of epidermal MCPIP1 is associated with aggressive squamous cell carcinoma

Abstract: Background Squamous cell carcinoma (SCC) of the skin is a common form of nonmelanoma skin cancer. Monocyte chemotactic protein 1-induced protein 1 (MCPIP1), also called Regnase-1, is an RNase with anti-inflammatory properties. In normal human skin, its expression is predominantly restricted to the suprabasal epidermis. The main aim of this study was to investigate whether MCPIP1 is involved in the pathogenesis of SCC. Methods We analyzed the distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Keratins are a large class of proteins produced by keratinocytes in the skin, hair, nails, and other cornified cells, and are closely related to the occurrence and development of SCC. [10][11][12][13] Studies have shown that KRT33B is significantly suppressed in low-grade gliomas and is associated with poor prognosis, [14] suggesting that this protein may be a marker for differentiation status, with high expression indicating better differentiation and prognosis. This is consistent with our results (Figure S1A, Supplemental Digital Content, http://links.lww.com/MD/K753 and Figure S2A, Supplemental Digital Content, http://links.lww.com/MD/ K754), where patients with low KRT33B expression had significantly worse outcomes than those with high expression.…”
Section: Discussionmentioning
confidence: 99%
“…Keratins are a large class of proteins produced by keratinocytes in the skin, hair, nails, and other cornified cells, and are closely related to the occurrence and development of SCC. [10][11][12][13] Studies have shown that KRT33B is significantly suppressed in low-grade gliomas and is associated with poor prognosis, [14] suggesting that this protein may be a marker for differentiation status, with high expression indicating better differentiation and prognosis. This is consistent with our results (Figure S1A, Supplemental Digital Content, http://links.lww.com/MD/K753 and Figure S2A, Supplemental Digital Content, http://links.lww.com/MD/ K754), where patients with low KRT33B expression had significantly worse outcomes than those with high expression.…”
Section: Discussionmentioning
confidence: 99%